Predictors of clinical outcome following transcatheter aortic valve implantation: a prospective cohort study - Huiberdina L Koek; Pieter R Stella; Lauren Dautzenberg; Judith E M Pals; Geert J Lefeber; Masieh Abawi; Marielle Emmelot-Vonk (Open Heart)
Objective In recent years, transcatheter aortic valve implantation (TAVI) has become the treatment of choice for patients with symptomatic aortic valve stenosis considered to be at increased or high surgical risk. The aim of this study was to identify predictors of postoperative adverse events in older adults undergoing TAVI.Methods A prospective observational cohort study of patients who were referred to a geriatric outpatient clinic for a geriatric assessment prior to TAVI was conducted. The outcomes were mortality and hospital readmission within 3 months of TAVI and the occurrence of major postoperative complications during hospitalisation according to the Clavien-Dindo classification. These three outcomes were also combined to a composite outcome. Univariate and multivariate logistic regression analyses were performed to identify predictors of the outcomes and composite outcome of adverse events.Results This cohort included 490 patients who underwent TAVI (mean age 80.7±6.2 years, 47.3% male). Within 3 months of TAVI, 19 (3.9%) patients died and 46 (9.4%) patients experienced a hospital readmission. A total of 177 (36.1%) patients experienced one or more major complications according to the Clavien-Dindo classification during hospitalisation and 193 patients (39.4%) experienced the composite outcome of adverse events. In multivariate analyses, cognitive impairment was identified as an independent predictor of major postoperative complications (OR 2.16; 95% CI 1.14 to 4.19) and the composite outcome of adverse events (OR 2.40; 95% CI 1.21 to 4.79). No association was found between the other variables and the separate outcomes and composite outcome.Conclusion Cognitive impairment is associated with postoperative adverse events in older patients undergoing TAVI. Therefore, it is important to screen for cognitive impairment prior to TAVI and it is recommended to include this in current TAVI guidelines.